HUBUNGAN KECERDASAN EMOSIONAL DENGAN RESILIENSI PADA WANITA PASCA BENCANA BANJIR - Uswatun Hasanah Kartika Sari; Iwan Purnawan; Arif Imam Hidayat (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
A disaster can have a wide range of effects, both physically and mentally. When tragedy strikes, women are particularly vulnerable and their resilience decreases. Someone who is in good psychological health normally has good interpersonal interactions, which influences emotional intelligence. The aim of this study is to discover a connection between emotional intelligence and resilience in women experiencing a flood disaster. This study was a correlational research with cross sectional design. This study was conducted out in Sirau Kemranjen, Banyumas Regency. This study’s sampling method was simple random sampling, which yielded 87 respondents. This study utilized an emotional intelligence and resilience instrument adapted from previous studies. Somers’d test was used to interpret the data in this analysis.